Studies on Raman Spectra of Cu2+ Ion Doped B2O3-K2O-ZnO-BaO Glasses (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Glasses with compositions 59B2O3-10K2O-(30-x)ZnO-xBaO-1CuO were prepared using melt quenching technique. The effect of BaO content in present glass system doped with copper ion in place of ZnO has been studied with respect to structural properties. Raman spectroscopy is an experimental technique appropriate for providing information about Â the structure, local arrangement of the atoms in the present glasses. The Raman spectra of glasses were recorded at room temperature in the range 200-1800 cm-1 using a He-Ne excitation source having wavelength 632.81 nm. The Raman peaks appeared around 760 cm-1 assigned symmetric breathing vibrations of six-membered ring with both BO3 triangle and BO4 tetrahedral. The intensity of these peaks is slightly varied with the addition of BaO content while the broadness is found to be larger at 30 mol% of BaO than 30 mol% ZnO. This indicates that certain BO4 units could be preferentially converted while those in ring groups could be stabilized. Raman studies it is concluded that present glasses are composed of [BO4] and [BO3] units in metaborate, orthoborate, diborate groups.